Integrating ICT and Generative AI in Classrooms for Sustainable Development: The Case of Schools in Nepal - Baral, Dilliram (Academia Journal of Humanities & Social Sciences, 2025)
This study aims to explore how ICT and AI are integrated into the classroom, emphasizing their impacts on teaching and learning. At a time when global education is extensively using digital tools, this study intends to discover how ICT and AI enhance better learning and teaching, ensuring digital literacy and reducing learning inequalities. ICT and AI provide quality education with personalized learning experiences enabling the real time assessment of students and empowering the marginalized communities to get an access to the mainstream education system. Additionally, the integration of ICT and AI helps reduce the use of papers in the classrooms and replace them with the digital learning materials. This increases energy-efficient, environmentally friendly school management ensuring sustainable development. The research design encompasses a mixed-methods approach, where the data have been collected through the questionnaires and interviews with the participation of selected teachers, students, and administrators from different schools in Pokhara Metropolitan City in Nepal. The preliminary findings showed that despite a high degree of interest in the adoption of ICT and AI, a bottleneck exists due to the inadequate infrastructural capacity, lack of teacher training for such technologies, and limited availability of advanced technology. The schools that have integrated the ICT tools such as interactive whiteboards and online learning platforms into the classrooms demonstrated improved engagement and academic outcomes among students. AI applications, like the personalized learning systems, would offer the customized learning experiences, especially in mathematics and languages. The study also demonstrated that these technologies need a policy enabling a framework, along with a cooperation among the government, educational institutions, and the private sector, which can surmount the barriers for an effective integration. The study will, therefore, be of great use to educators, policymakers, and other stakeholders with recommendations on how best the schools can make use of technology and at the same time advance equal opportunities for quality education. Further research is recommended to explore the long-term impact of these technologies on the student learning outcomes.